Implementation of Good Governance on Fraud Prevention at Village Credit Institutions Buleleng Regency - Rahayu, Sri; Diatmika, I Putu Gede (Valid: Jurnal Ilmiah, 2023)
The Village Credit Institution (LPD) is a dynamic company that can encourage economic growth and financial institutions are held by the local government, the management of which is carried out by traditional villages in the Province of Bali. Good governance can be interpreted as an efficient public service, a reliable control system, a government that is accountable to its public. This study uses a quantitative approach. The design of this study will test the hypothesis by means of multiple linear regression using partial least square measurements. Fraud Prevention has a t-test significance value of 0.005, this value is less than 0.05. So, it can be concluded that the implementation of good governance has a significant effect on fraud prevention.